Development of novel phenoxy-diketopiperazine-type plinabulin derivatives as potent antimicrotubule agents based on the co-crystal structure. Issue 1 (1st January 2020) - Ding, Zhongpeng; Ma, Mingxu; Zhong, Changjiang; Wang, Shixiao; Fu, Zhangyu; Hou, Yingwei; Liu, Yuqian; Zhong, Lili; Chu, Yanyan; Li, Feng; Song, Cai; Wang, Yuxi; et al.
Graphical abstract: Abstract: The co-crystal structure of Compound 6b with tubulin was prepared and solved for indicating the binding mode and for further optimization. Based on the co-crystal structures of tubulin with plinabulin and Compound 6b, a total of 27 novel A/B/C-rings plinabulin derivatives were designed and synthesized. Their biological activities were evaluated against human lung cancer NCI-H460 cell line. The optimum phenoxy-diketopiperazine-type Compound 6o exhibited high potent cytotoxicity (IC50  = 4.0 nM) through SAR study of three series of derivatives, which was more potent than plinabulin (IC50  = 26.2 nM) and similar to Compound 6b (IC50  = 3.8 nM) against human lung cancer NCI-H460 cell line. Subsequently, the Compound 6o was evaluated against other four human cancer cell lines. Both tubulin polymerization assay and immunofluorescence assay showed that Compound 6o could inhibit microtubule polymerization efficiently. Furthermore, theoretical calculation of the physical properties and molecular docking were elucidated for these plinabulin derivatives. The binding mode of Compound 6o was similar to Compound 6b based on the result of molecular docking. The theoretical calculated LogPo/w and PCaco of Compound 6o were better than Compound 6b, which could enhance its cytostatic activity. Therefore, Compound 6o might be developed as a novel potent anti-microtubule agent.